Pharmacological effects of the association between antihypertensives and non-steroid anti-inflammatory agents: an updated review (Research, Society and Development, 2022)
Systemic Arterial Hypertension (SAH) is considered a chronic multifactorial degenerative disease and a polygenic syndrome. Antihypertensive pharmacotherapy usually starts with first-line antihypertensive medications as monotherapy or in combination, which may be preferable in elderly patients with higher blood pressure (BP) levels. Aging is also accompanied by a considerable increase in the use of other medications, highlighting the use of analgesic and anti-inflammatory drugs, such as non-steroidal anti-inflammatory drugs (NSAIDs). Therefore, the aim of this review is to demonstrate the possible interactions between antihypertensives and NSAIDs, as well as highlight the main adverse reactions caused by such interactions, according to data published in the last five years. A review of the scientific literature, national and international, which contained in their titles and/or abstracts the following descriptors was carried out: systemic arterial hypertension, antihypertensives, anti-inflammatory drugs, NSAIDs. The use of multidrug therapy brings constant concern about drug interactions and the adverse effects that result from it. The analyzed studies report the use of antihypertensives (mainly inhibitors of the renin-angiotensin system) associated with NSAIDs and their consequences, such as cardiovascular diseases, nephrotoxicity and hyperkalemia. It is believed that the rational and adequate prescription of these drugs can minimize the adverse effects resulting from drug interactions.